The socio-materiality of learning practices and implications for the field of learning technology - Aditya Johri (Association for Learning Technology, 2011)
Although the use of digital information technologies in education has becomecommonplace, there are few, if any, central guiding frameworks or theories thatexplicate the relationship between technology and learning practices. In thispaper, I argue that such a theoretical framework can assist scholars and practitionersalike by working as a conduit to study and design learning technologies.Towards this goal, I propose socio-materiality as a key theoretical construct withvaluable insights and implications for the field of learning technology. Sociomaterialityhelps balance the disproportionate attention given to either the socialimplications of technology use or the material aspects of technology design.Furthermore, I forward ‘socio-material bricolage' as a useful analytical frameworkto examine and design technology-infused learning environments. I illustratethe value of the framework by applying it to three case studies of formaland informal technology-based learning.